2022
DOI: 10.3390/pharmaceutics14071416
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome Sulfotransferases: Mode of Action, Expression and Localization

Abstract: Oxamniquine (OXA) is a prodrug activated by a sulfotransferase (SULT) that was only active against Schistosoma mansoni. We have reengineered OXA to be effective against S. haematobium and S. japonicum. Three derivatives stand out, CIDD-0066790, CIDD-0072229, and CIDD-0149830 as they kill all three major human schistosome species. However, questions remain. Is the OXA mode of action conserved in derivatives? RNA-interference experiments demonstrate that knockdown of the SmSULT, ShSULT, and SjSULT results in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This might be associated with the level of Sm SULT transcript. The expression of Sm SULT in male worms increases in 21 dpi, 28 dpi reaching the highest levels at day 35 dpi [ 36 38 ]. Similar to male worms, female worms’ Sm SULT transcript increases in 21 dpi, peaks at day 28 dpi, but then begins to decrease [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be associated with the level of Sm SULT transcript. The expression of Sm SULT in male worms increases in 21 dpi, 28 dpi reaching the highest levels at day 35 dpi [ 36 38 ]. Similar to male worms, female worms’ Sm SULT transcript increases in 21 dpi, peaks at day 28 dpi, but then begins to decrease [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we anticipate the SULT active site will accommodate further modifications to our most active compounds as we fine tune them to increase favorable pharmacokinetic properties. Our studies demonstrated that OXA derivative 790 has the same mode of action as OXA [ 38 ]. Knockdown of Sm SULT using RNA-interference ( S2 Fig ) results in resistance to 830 , 610 and 303 treatments, confirming that the mode of action is conserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified Schistosoma mansoni sulfotransferase ( Sm SULT) to be one of the attractive drug targets for rational drug design to treat schistosomiasis. 28 , 29 Sulfotransferases catalyse the transfer of a sulfuryl group from a sulphate donor to substrates. 29 Therefore, inhibition of the Sm SULT is fatal to the organism.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 Sulfotransferases catalyse the transfer of a sulfuryl group from a sulphate donor to substrates. 29 Therefore, inhibition of the Sm SULT is fatal to the organism. The past effectiveness of oxamniquine against S mansoni infections in Brazil has validated Sm SULT as a viable drug target.…”
Section: Introductionmentioning
confidence: 99%